Review on monitoring natural and environmental radiation and its potential from mining products - Imam Ghazali Yasmint (Institut Teknologi Bandung, 2021)
Monitoring of natural radiation in Indonesia has been carried out by various parties, from researchers, academics at universities to special agencies tasked with handling this matter, such as the National Nuclear Energy Agency (Batan) and the Nuclear Energy Supervisory Agency (Bapeten). Batan through the Center for Radiation Safety and Metrology Technology (PTKMR) is in charge of monitoring natural radiation at the national level. The purpose of this paper is to review the monitoring of natural and environmental radiation in Indonesia and the potential of mining products as a source of natural radiation. The mining products that will be reviewed in this paper are natural uranium and thorium which are usually found in several mines, such as tin mines and others.